Halting Antipsychotic Use in Long-Term care (HALT): a single-arm longitudinal study aiming to reduce inappropriate antipsychotic use in long-term care residents with behavioral and psychological symptoms of dementia. (7th March 2017) - Jessop, Tiffany; Harrison, Fleur; Cations, Monica; Draper, Brian; Chenoweth, Lynn; Hilmer, Sarah; Westbury, Juanita; Low, Lee-Fay; Heffernan, Megan; Sachdev, Perminder; Close, Jacqueline; Blennerhassett, Jenny; et al.
ABSTRACT: Background: Inappropriate use of antipsychotic medications to manage Behavioral and Psychological Symptoms of Dementia (BPSD) continues despite revised guidelines and evidence for the associated risks and side effects. The aim of the Halting Antipsychotic Use in Long-Term care (HALT) project is to identify residents of long-term care (LTC) facilities on antipsychotic medications, and undertake an intervention to deprescribe (or cease) these medicines and improve non-pharmacological behavior management. Methods: LTC facilities will be recruited across Sydney, Australia. Resident inclusion criteria will be aged over 60 years, on regular antipsychotic medication, and without a primary psychotic illness or very severe BPSD, as measured using the Neuropsychiatric Inventory (NPI). Data collection will take place one month and one week prior to commencement of deprescribing; and 3, 6 and 12 months later. During the period prior to deprescribing, training will be provided for care staff on how to reduce and manage BPSD using person-centered approaches, and general practitioners of participants will be provided academic detailing. The primary outcome measure will be reduction of regular antipsychotic medication without use of substitute psychotropic medications. Secondary outcome measures will be NPI total and domain scores, Cohen-Mansfield Agitation Inventory scores and adverse events, including falls and hospitalizations. Conclusion: While previous studies have described strategies to minimize inappropriate use of antipsychotic medications in people with dementia living in long-term care, sustainability and a culture of prescribing for BPSD in aged care remain challenges. The HALT project aims to evaluate the feasibility of a multi-disciplinary approach for deprescribing antipsychotics in this population.